(untitled) (Journal of Informatics Education and Research, 2023)
This research paper explores the gender-specific consequences of the COVID-19 pandemic on work and family dynamics. It highlights the deep-rooted societal circumstances and mechanisms that have resulted in gender disparities in both the workplace and domestic sphere. The study emphasizes the importance of considering variations based on factors such as race, socioeconomic status, and marital/parental status in work and family studies. The paper discusses the uneven impact of the pandemic on women, including job losses and increased caregiving responsibilities. It also examines the potential disruptions to pre-existing gender disparities and the need for further research on the lasting consequences of the pandemic on gender inequality or equality. Additionally, the effects of employment fluctuations on women’s professional trajectories and economic standings, as well as the potential transformations in care systems and work institutions after the pandemic.